2021
DOI: 10.1016/j.ijregi.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine acceptance among healthcare workers in the United Arab Emirates

Abstract: Background COVID-19 vaccine hesitancy among healthcare workers (HCWs) is a threat to any healthcare system. Vaccine hesitancy can increase infection risk among HCWs and patients, while also impacting the patients’ decision to accept the vaccine. Our study assessed COVID-19 vaccine acceptance among HCWs in United Arab Emirates (UAE). Methods Using purposive sampling, UAE HCWs registered in the Abu Dhabi Department of Health (DOH) email database were invited to complete a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
(23 reference statements)
2
14
2
Order By: Relevance
“…The vaccine choice is with Sinopharm in the lead (75%) when compared to Pfizer (23%). This is similar to a study conducted among healthcare workers who preferred Sinopharm [13] . Most parents have taken the Sinopharm vaccine, and most of them like it for their children.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The vaccine choice is with Sinopharm in the lead (75%) when compared to Pfizer (23%). This is similar to a study conducted among healthcare workers who preferred Sinopharm [13] . Most parents have taken the Sinopharm vaccine, and most of them like it for their children.…”
Section: Discussionsupporting
confidence: 89%
“…This was seen from the early stages and in all aspects, such as healthcare capacity and non-pharmacological and pharmacological interventions accessibility. For example, COVID-19 testing and adult COVID-19 vaccination were accepted well by the UAE population, and this was reflected in the high acceptance rates reported, compared to other countries in the world [4] , [5] , [13] [14)], as well as a comparatively lower mortality rate [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the respondents showed good acceptance of COVID-19 vaccine, as the average mean score for the items regarding the same was 3.55 out of 5. In this context, a study among healthcare workers in the neighboring country of the UAE reported that vaccine acceptance was high (>89%) ( 19 ). Similar finding was reported from the same population in Kuwait ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 18. , 19. In this study unlike in previous studies, it was shown that signing the pre-vaccination informed consent form affects vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%